The potential of integrated project delivery in greening the structural steel delivery process - Gotthelf, Helene Nathalie, author; Ozbek, Mehmet Egemen, advisor; Guggemos, Angela Acree, committee member; Taylor, Pete, committee member (Colorado State University. Libraries, 2011)
The structural steel industry provides the world with one of the fundamental construction materials, steel, and in the process produces negative byproducts. While the steel industry has made commendable progress to reduce their environmental impacts, there remains room for improvement, particularly in the delivery process of structural steel. Currently, the majority of the structural steel industry uses traditional delivery methods to execute design, engineering, detailing, fabrication, and erection. Construction industry professionals are realizing the drawbacks of traditional delivery systems and are now exploring the opportunities provided by Integrated Project Delivery (IPD).The researcher studied the potential that IPD could have on lessening the environmental impacts of the steel industry through a case study of the National Renewable Energy Laboratory (NREL) Research Support Facilities (RSF) project. Data was collected through interviews with NREL RSF project team members. Data analysis revealed thirty opportunities for improvement to reduce the environmental impacts associated with the delivery of structural steel. Overarching process recommendations expand on the need to establish direct lines of communication among the structural steel team, ensure early involvement of the erector and fabricator in the steel design phase, and utilize appropriate technology.
Keywords: energy efficiency; construction; delivery method; erector; fabricator; integrated project delivery